ILLOCUTIONARY ACTS UTTERED BY THE MAIN CHARACTER IN “THE VOW” MOVIE - Ramadhani, Sri; Mustikawati, Yunitari (Journal of English Literature and Linguistic Studies, 2023)
The Vow movie has been selected by the researcher as the study's subject. “The Vow” is a romantic comedy directed by Michael Sucsy that aired in 2012. This movie is inspired by a real story. The movie is about a husband and wife named Leo and Paige. They had just come out of the cinema, but on the way home they had an accident which resulted in Paige (Leo’s wife) experiencing a severe brain injury, so that Paige’s memory for the last 5 years was lost. So Paige forgot all her memories of her husband (Leo). In this study, the researcher discusses the use of illocutionary acts. The researcher focuses on identifying the types of illocutionary acts and examine the meanings of the illocutionary acts uttered by the main character in “The Vow” movie. In determining this, the researcher uses the theory by John R. Searle (1979). In researching the problem the researcher used a qualitative descriptive method. The researcher watched the movie several times and then transcribed the movie for research. The results of this study are all the types of illocutionary acts namely; representative, directive, commissive, expressive, and declaratives, as found in “The Vow” movie. The researcher has found 56 utterances in total which stated by the main characters Leo and Paige. The first type is Representatives, and the researcher found 23 utterances. The second type is directives, and the researcher found 20 utterances. The third type is commissive, and the researcher found 4 utterances. The fourth type is Expressives, and the researcher found 7 utterances, The last type is Declaratives, in this type the researcher found 3 utterances and they are 3 deciding. So, the researcher found all the types of illocutionary acts in “The Vow” movie